Looking after health: a joint working approach to improving the health outcomes of looked after and accommodated children and young people - Anne Grant; John Ennis; Fiona Stuart (Scottish Journal of Residential Child Care)
Looked after and accommodated children and young people represent one of the most vulnerable groups within our society. Inequality and disadvantage impact upon every aspect of their lives, but the health inequalities which they suffer are particularly disturbing. If we are to improve the health outcomes of these young people, then all agencies must commit themselves to working together. Only if we foster a joint working approach can we hope to make a positive impact upon what are wholly unacceptable health outcomes.